Long live the screw pines - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
The multipurpose screw pine tree (Pandanus tectorius) is an important source of food, medicine and building material in the Pacific nation of Kiribati, but it is an endangered species.A joint programme by the FAO, the South Pacific Community and the...